Performance analysis of deterministic key allocation schemes for wireless sensor networks. (17th July 2012) - Gupta, Abhishek; Kuri, Joy; Sanyal, Sugata
Because of the resource-constrained nature of Wireless Sensor Networks (WSNs), it is easier to use a security system based on symmetric key cryptography. However, the distribution and management of cryptographic keys pose challenges of their own. In this paper, we study some deterministic methods of distribution of keys to nodes. We propose and analyse a polynomial-based scheme and a complete connectivity scheme. An analytical comparison between the schemes, in terms of security and connectivity, is presented next. Motivated by the schemes, we present a general key allocation scheme and derive general expressions for security and connectivity that are applicable to any deterministic key distribution algorithm in a certain class (not just the polynomial and full-connectivity schemes mentioned above). With the help of these expressions, we present a number of trade-offs which should be taken into account while designing a secure system.